Evaluation of “One Body, One Life”: A Community-Based Family Intervention for the Prevention of Obesity in Children - Marsha Towey; Ruth Harrell; Berni Lee (Journal of Obesity)
Service evaluation of a community-based healthy lifestyle programme, designed for families aimed at preventing obesity. Physiological and behaviour measures were recorded at the beginning and end of the programme. Out of a total of 454 participants, 358 (79%) completed. From these completers 293 (64%) were analysed as there was sufficient data. The use of “high visibility recruitment” led to 77% of completers being from Coventry's two most deprived population quintiles. Ethnic minorities were also well represented. There were statistically significant self-reported behaviour changes, with improvements in fruit and vegetables eaten and decrease in consumption of crisps, snacks, and take away foods. There were also significant increases in physical activity. There were small but statistically significant improvements in BMI/BMI percentile for adults and children who started the programme overweight/obese. These results demonstrate the programmes' effectiveness in enabling behaviour change, and attracting participants from deprived communities.